Market dynamics of biodegradable bio-based plastics: Projections and linkages to European policies - Niklas Döhler; Claudia Wellenreuther; André Wolf (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2020)
This paper analyzes the future market perspectives for biodegradable bio-based plastics at the global and the European level. Relevant determinants of demand are identified, categorized and used as a basis for own projections. By implementing a system dynamics approach, the evolution of global production capacities is modelled on an annual basis for the period until 2030. To capture the inherent uncertainty in such a long-term projection, different scenarios are defined and applied to the model, reflecting different developments in GDP growth, oil and bioplastic feedstock prices. In this way, our results document the sensitivity of the bioplastics market towards changes in the macroeconomic environment. The simulations are complemented by a discussion of the relevant regulatory framework at the European level and its potential repercussions on market growth. The results indicate a significant growth potential, which however turns out to be very sensitive towards both economic and political impact factors.
Keywords: Q57; L65; Q21; 330; Bioplastics; System Dynamics; European Plastic Policies; Bioeconomy